Impact of TNF inhibitor therapy on joint replacement rates in rheumatoid arthritis: a matched cohort analysis of BSRBR-RA UK registry data. (10th January 2019) - Hawley, Samuel; Ali, M Sanni; Cordtz, René; Dreyer, Lene; Edwards, Christopher J; Arden, Nigel K; Cooper, Cyrus; Judge, Andrew; Hyrich, Kimme; Prieto-Alhambra, Daniel
Abstract: Objectives: Previous ecological data suggest a decline in the need for joint replacements in RA patients following the introduction of TNF inhibitor (TNFi) therapy, although patient-level data are lacking. Our primary aim was to estimate the association between TNFi use and subsequent incidence of total hip replacement (THR) and total knee replacement. Methods: A propensity score matched cohort was analysed using the British Society for Rheumatology Biologics Registry (2001–2016) for RA data. Propensity score estimates were used to match TNFi users to similar conventional synthetic DMARD users (with replacement) using a 1:1 ratio. Weighted multivariable Cox regression was used to estimate the impact of TNFi on study outcomes. Effect modification by baseline age and disease severity were investigated. Joint replacement at other sites was also analysed. An instrumental variable sensitivity analysis was also performed. Results: The matched analysis contained a total of 19 116 patient records. Overall, there was no significant association between TNFi use vs conventional synthetic DMARD on rates of THR (hazard ratios = 0.86 [95% CI: 0.60, 1.22]) although there was significant effect modification by age ( P < 0 .001). TNFi was associated with a reduction in THR among those >60 years old (hazard ratio = 0.60 [CI: 0.41, 0.87]) but not in younger patients. No significant associations were found for total knee replacement or other joint replacement. Conclusion: Overall, no association was found between the use of TNFi and subsequent incidence of joint replacement. However, TNFi was associated with a 40% relative reduction in THR rates among older patients.